Histopathological Changes of Testes and Testosterone Level of Mice that are Exposed to Permot Leaf Mosquito Mat (Passiflora foetida) - Rina Priastini Susilowati (UNIVERSITAS NEGERI PADANG, 2019)
In this study, mice testicular degeneration was influenced by exposure to the mosquito mat made from transfluthrin 3000 ppm and permot leaf mosquito mat which were evaluated based on observations on testicular histopathological changes and testosterone level. Fifteen Balb C male mice aged 2-3 months with a body weight of 25-30 g were divided into five groups, namely A, B, C, D, and E, with each group consisting of 3 replications. Group A was the negative control group (without exposure), group B was the exposure group for the mosquito mat made from transfluthrin 3000 ppm, group C, D, and E were the exposure groups of mosquito mat with permot leaves doses of 1000 ppm, 2000 ppm and 3000 ppm. Each exposure group was given treatment 8 hours per day from 18.00 - 04.00 for 3 months. The results showed a significant decrease in testicular weight between the control group and the treatment group. There were also significant differences in the testosterone level observed in the treatment group, as well as observations on the spermatogenic index (IS). For histopathological observation of testicular mice, there was a reduction in epithelial cell spermatogenic and diameter of seminiferous tubule. The results of the Kruskall Wallis test showed a significant difference between the control group and the treatment group of the mosquito mat made from transflutrin 3000 ppm. The conclusion is that exposure to mosquito mat made of permot peaves up to a 3000 ppm dose is safe to use and can kill the Aedes aegypti mosquito effectively.